Reaksi Investor Pasar Modal terhadap Event Pengumuman Paket-Paket Kebijakan Ekonomi Jokowi-Jusuf Kalla - Handayani, Revita Dwi; Kesuma, Wendy (Keizai, 2021)
The purpose of this study is to examine whether the Economic Policy Package issued by the Government of President Jokowi-Jusuf Kalla can be used to see the reaction of Capital Market Investor that can be seen from abnormal returns received by investors. The abnormal return calculation method used in this research is CAPM (Capital Asset Pricing Model). The results of this study obtained that the announcement of the Economic Policy Package issued by the Government Jokowi - Jusuf Kalla does not affect the reaction of investors in the capital market, and it also applies to other variables.